The aesthetic concepts of the art of preparing the space as an introduction to the development of innovative plastic formulations for ceramic pieces (Al-Academy, 2025)
current research aims to identify the aesthetic concepts for the art of preparing the space, to create an innovative drafting formula for ceramics, and to achieve this, a semi-experimental descriptive approach was used, and it consisted of a group of ceramic pieces, which is: (ceramic cup, vase, plate, collection of ceramic drops, ceramic jar) To convert them from utilitarian ceramic pieces into aesthetic works, and it became clear from the research results that the aesthetic concepts for the art of preparation in space influenced the visual thinking and the aspect by creating ceramic pieces, as creativity achieved a modern aesthetic vision of ceramic pieces through the art of processing in space, and we was taken advantage of utilitarian pieces and ceramics by transforming them into aesthetic works equipped in the space